2001
DOI: 10.1046/j.1432-1327.2001.01885.x
|View full text |Cite
|
Sign up to set email alerts
|

UV‐A‐related alterations of young and adult lens water‐insoluble α‐crystallin, plasma membranous and cytoskeletal proteins

Abstract: The damaging effects of UV-A irradiation on lens waterinsoluble a-crystallin, plasma membranous and cytoskeletal proteins derived from bovine lenses were studied. Young and adult bovine lenses were kept viable for 2 months in organ culture. After 24 h of incubation they were irradiated, and analyses of the proteins by one-dimensional and two-dimensional gel electrophoresis followed by Western blotting were carried out at several time intervals. RNA isolation, PCR and Northern blotting were also performed. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 39 publications
1
21
0
2
Order By: Relevance
“…We showed that UVinduced morphological changes were associated with actin cytoskeleton reorganization and characterized, at least in part by the disruption of actin stress fibres and cell-cell adhesions. Several other studies also revealed that UV radiation induced the actin cytoskeleton reorganization leading to the destruction of cell adherence and consequently to cell death [10,18,19]. In addition, we noticed that F-actin was presented in the form of dense ring-like structures surrounding the nuclei of cells with apoptotic-like phenotype.…”
Section: Discussionsupporting
confidence: 56%
“…We showed that UVinduced morphological changes were associated with actin cytoskeleton reorganization and characterized, at least in part by the disruption of actin stress fibres and cell-cell adhesions. Several other studies also revealed that UV radiation induced the actin cytoskeleton reorganization leading to the destruction of cell adherence and consequently to cell death [10,18,19]. In addition, we noticed that F-actin was presented in the form of dense ring-like structures surrounding the nuclei of cells with apoptotic-like phenotype.…”
Section: Discussionsupporting
confidence: 56%
“…In this case, an increase of the molecular chaperone, the HSP70 protein, might play a role in preventing lens proteins such as crystallins from aggregation. This idea is supported by reports that heat shock and UV-A irradiation, known to cause aggregation of lens proteins (Blondin and Taylor, 1987;Wong et al, 1978), caused an increase in the hsp70 expression in lens (Lang et al, 2000;Weinreb et al, 2001). The similar response of hsp70 and ␣A-crystallin to ⌬g is probably due to similar properties of their protein products in lens.…”
Section: Microgravity Vs Hypergravitymentioning
confidence: 65%
“…During development, hsp70 plays an essential role in lens formation (Evans et al, 2005). Later, when lens proteins such as crystallins play a role in the maintenance of lens cell transparency, Hsp70 is thought to protect the lens proteins from aggregation caused by environmental stresses such as heat and cold shock, ultraviolet-A (UV-A) irradiation, and oxidative stress (de Jong et al, 1986;Weinreb et al, 2001;Bagchi et al, 2002;Banh et al, 2003). Recent studies with cultured cells also demonstrated that microgravity exposure changed the expression level of hsp70 (Carlsson et al, 2003;Kumei et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…An investigation conducted with Chinese hamster ®broblasts (Banrud et al, 1999) found that while biologically-relevant uences of UVA were able to disintegrate actin ®laments in the cells, even lethal¯uences of UVB light had no effect on the proteins. Studies with cultured lenses have also indicated distinct damaging effects of UVA light on cytoskeletal proteins (Rafferty et al, 1993;Zigman et al, 1996;Weinreb et al, 2001); however, these studies investigated only damage to proteins present in the lens epithelium and cortex. The¯uences of UVA light used in the cultured lens work were at least 5±10 times higher than ours, which may be why the previous investigators were able to induce UVA damage in the epithelium and cortex, whereas we could not.…”
Section: Discussionmentioning
confidence: 99%